Studi Pendahuluan Perilaku Hidup Bersih dan Sehat Siswa di Kelas IV SD Islam Nibras Kota Padang - Abdul Halim (Kilau Publishing, 2023)
This research aims to determine and obtain preliminary data on the clean and healthy living behaviors of fourth-grade students at SD Islam Nibras in Padang City. This study is a quantitative descriptive research. The subjects of this research are ten fourth-grade students at SD Islam Nibras Padang. Data sources for this research were obtained through observation sheets and questionnaires. The data from the observation sheets were quantitatively analyzed in the form of percentages. The preliminary research results show that approximately 20% of students can be categorized as successful or able to demonstrate clean and healthy living behaviors in the excellent and good categories. Around 80% of students have not been able to demonstrate their behavior as satisfactory or less good. The results of this research can be concluded that the clean and healthy living behaviors of fifth-grade students at SD Islam Nibras are still in the less good category.